Impact of Cyclic Loading on Chloride Diffusivity and Mechanical Performance of RC Beams under Seawater Corrosion - Sen Pang; Bo Diao; Yinghua Ye; Shuxin Chen; Xin Wang (Advances in Materials Science and Engineering)
An experimental study was conducted to investigate the impact of cyclic loading on the mechanical performance and chloride diffusivity of RC beams exposed to seawater wet-dry cycles. To induce initial damage to RC beam specimen, cyclic loading controlled by max load and cycles was applied. Then beam specimens underwent 240 wet-dry cycles of seawater. Results show that the chloride content increased as max load and cycle increased. The chloride content at steel surface increased approximatively linearly as average crack width increased. Moreover, the max load had more influence on chloride content at steel surface than cycle. The difference of average chloride diffusion coefficient between tension and compression concrete was little at uncracked position. Average chloride diffusion coefficient increased as crack width increased when crack width was less than 0.11 mm whereas the increasing tendency was weak when crack width exceeded 0.11 mm. The residual yield load and ultimate load of RC beams decreased as max load and cycle increased. Based on univariate analysis of variance, the max load had more adverse effect on yield load and ultimate load than cycle.